2003
DOI: 10.1002/humu.10182
|View full text |Cite
|
Sign up to set email alerts
|

TP53 mutations in workers exposed to occupational carcinogens

Abstract: For the p53 Special IssueIn some cases, evidence exists that exogenous carcinogenic exposures contribute to the mutation spectrum of the TP53 gene (p53) in human cancers. Although the clearest examples come from dietary and environmental sources, only a restricted number of papers have concentrated specifically on TP53 mutations in tumors from workers exposed to occupational carcinogens. In populations exposed to dietary aflatoxin B1 with liver cancer (AFB1) and ultraviolet (UV)-radiation with skin cancer, a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 113 publications
1
16
0
1
Order By: Relevance
“…For example, missense mutations within pancreatic cancers predominantly occur within the MH1 domain or the MH2 domain COOH-terminal to the MCR, whereas those mutations affecting gastrointestinal mucosa (small bowel or colorectal carcinomas) occur more frequently within the MCR. Tumor type clustering of mutations as a function of environmental influences is a recognized phenomenon of other genes known to be important in carcinogenesis, such as p53 and K-ras (48,49). Thus, differential influences may exist that contribute to the mutational spectrum of MADH4.…”
Section: Discussionmentioning
confidence: 99%
“…For example, missense mutations within pancreatic cancers predominantly occur within the MH1 domain or the MH2 domain COOH-terminal to the MCR, whereas those mutations affecting gastrointestinal mucosa (small bowel or colorectal carcinomas) occur more frequently within the MCR. Tumor type clustering of mutations as a function of environmental influences is a recognized phenomenon of other genes known to be important in carcinogenesis, such as p53 and K-ras (48,49). Thus, differential influences may exist that contribute to the mutational spectrum of MADH4.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, AFB1-N 7 -Gua and AFB1-FAPy can induce error-prone DNA repair and result in the damage of DNA strands, including double-strand breaks (DSBs), single-strand breaks (SSBs), base pair substitution, frame shift mutations, and oxidation DNA damage such as 8-oxodeoxyguanosine (8-oxyG) [25][26][27][28]. For genes mutations induced by AFB1 exposure, G:C > T:A mutation in codon 249 of TP53 gene has been frequently reported [29][30][31][32][33][34][35][36]. This mutation is tested in more than 40% of HCC from high-AFB1-exposure areas, but in either very rare or absent for those from low or null AFB1 exposure areas [36][37][38][39].…”
Section: Dna Damage Induced Byafb1 and Dna Repairmentioning
confidence: 99%
“…Recent studies have shown that the levels of AFB1-DNA adduct of the peripheral blood white cells are positively and lineally correlated with that of liver cells, implying analysis of AFB1-DNA adducts in the peripheral blood white cells may substitute for the elucidation of tissular levels of adducts (39,41). For genes mutations induced by AFB1 exposure, the experimental and theoretical researches are briefly on the p53 gene (42)(43)(44)(45)(46)(47)(48)(49). Reaction with DNA at the N 7 position of guanine preferentially causes a G:C > T:A mutation in codon 249 of this gene, leading to an amino acid substitution of arginine to serine (44)(45)(46)(47)(48)(49)(50).…”
Section: Afb1 Exposure and Dna Damage And Repairmentioning
confidence: 99%
“…For genes mutations induced by AFB1 exposure, the experimental and theoretical researches are briefly on the p53 gene (42)(43)(44)(45)(46)(47)(48)(49). Reaction with DNA at the N 7 position of guanine preferentially causes a G:C > T:A mutation in codon 249 of this gene, leading to an amino acid substitution of arginine to serine (44)(45)(46)(47)(48)(49)(50). In high AFB1-exposure areas, this mutation is present in more than 40% of HCC and can be detected in serum DNA of patients with preneoplastic lesions and HCC (41).…”
Section: Afb1 Exposure and Dna Damage And Repairmentioning
confidence: 99%